The natural history of bone stress injuries in athletes: from inception to resolution - Crunkhorn, M. L.; Etxebarria, N.; Toohey, L. A.; Charlton, P.; Watson, K.; Drew, M. (Sports Medicine, 2025)
Bone stress injury (BSI) occurrence is common in athletic populations, resulting in high periods of time loss from sports participation. Minimising incidence and reducing severity presents a challenge for the prevention and clinical management of bone stress injuries (BSIs) for sports practitioners. An understanding of the aetiology and mechanisms for BSIs in athletic populations can assist with the design and implementation of prevention programmes. Application of established health frameworks allows practitioners to identify and manage the complex and dynamic interplay of factors that alter the susceptibility of an athlete to the onset, and subsequent progression of BSIs. The natural history of disease describes well-defined sequential stages of disease progression, sequenced from pathological onset through to disease outcome that occurs in the absence of clinical intervention. The purpose of this review is to synthesise and map the current evidence on BSIs to the natural history of disease. This review will provide sports medicine practitioners with a clinically applied framework that aligns current evidence to stages of disease, with reference to intervention and management. In addition, targeted prevention strategies are described and mapped to primary, secondary and tertiary levels of prevention along the BSI continuum. Despite the extensive body of evidence detailing BSIs in sport, this paper is the first to integrate and map BSIs to the natural history of disease.